Reconstructing Mindanaoan vernacular architecture a study on the site and material selection of ethnolinguistic groups in central and sounthern Mindanao - Caintic, Michelle Belen (2014)
Vernacular architecture is referred to be the universe? manifestation and physical representation of the people?s advocacy for sustainability that has been characterized as the influence of the culture, religion, beliefs, socio-economic behavior and environmental aspects of the world that brought changes in the community. With the emergence of the need for restructuring the Mindanaoan Vernacular Architecture, this study has arrived into its existence. This study aims to develop a replica of the six ethno-linguistic groups in Mindanao namely: Maranao, B?laan, Bagobo, T?boli, Mandaya and Manobo. Each of this tribe has distinctions in their manner of construction from site selection, spatial arrangement and beliefs up to the intricate ornamentations and decorations they employ in their dwellings. The data are collated through identification of these Southern Mindanao Ethnolinguistic Lumad and Muslim dwellings and will be analyzed using Amos Rapoport?s Approach to develop Guidelines and Handbook of Reconstruction and Rehabilitation of Ethnolinguistic Vernacular Architecture. The designs from the evaluated results, will become the foundation for reconstructing the ethnolinguistic vernacular architecture and will be used for the development of multi-cultural complex and multi-cultural village. This will help in the future sustainable community that serves as replica of Mindanao?s culture and arts and a venue for the fusion of the six ethnolinguistic groups? culture that are becoming extinct due to urbanization eating up our society at present. Thus, in restructuring Mindanaoan Vernacular Architecture, it is necessary to deal with the living environment, not merely the built-up or existing sites and ensure that heritage policies directly benefit the six ethnolinguistic groups. Moreover, this study promotes a thorough research and development of the potentials evident in traditional technologies and enhancing environmental sustainability on energy consumption and maintenance. There is also a need to think of the future actions integrating human development, conservation and preservation in an attainable manner.